12-week training induced effects on selected fitness parameters among field hockey players - Kumar, R.; Lehri, A.; Singh, S.; Sharma, S. (International Journal of Physiology, Nutrition and Physical Education, 2019)
The purpose of this study was to assess effect of 12-week training on selected fitness parameters. 28 young field hockey players, were selected for the study. Variables change of direction speed (CODS), maximum speed, shoulder strength, leg strength and flexibility were measured two times with an interval of 12-weeks. Measurements obtained were compared using paired t-test to assess the effects of training. The level of significance was set at 0.05. Results shows that shoulder strength, maximum speed and leg strength found to be statistically significantat p <.01 while flexibility found to be statistically significant at p <.05. No statistically significant difference was found in case of CODS. It was concluded that selected training programme is proficient to develop general fitness of the players and can be used by the coaches. For improvement in CODS skill specific training alongside speed and strength training is necessary